2008
DOI: 10.4306/pi.2008.5.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alzheimer's Dementia and Its Risk Factors in Community-Dwelling Elderly Koreans

Abstract: ObjectiveWe estimated the prevalence of Alzheimer's dementia (AD) and mild cognitive impairment (MCI) and their risk factors in an urban community setting, focusing especially on metabolic syndrome.MethodsA two-phase investigation based on a door-to-door survey was performed. In Phase I, we administered the Korean version of the Mini-Mental State Examination (MMSE-KC) of the Consortium to Establish a Registry for Alzheimer's disease (CERAD-K). Assessment Packet and the Korean version of the Geriatric Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 47 publications
6
23
0
Order By: Relevance
“…For some evidences, an atrial fibrillation was relevant to cognitive impairment and hippocampal atrophy with no symptomatic stroke or silent infarction. 34,35 The previous studies 26,30,31,[36][37][38][39] and the results of our study have shown that atrial fibrillation was associated with an increased risk of poststroke dementia. Moreover, the result of this study found that stroke patients with atrial fibrillation risk of dementia were 1.68 times compared with stroke patients without atrial fibrillation statistically significant.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…For some evidences, an atrial fibrillation was relevant to cognitive impairment and hippocampal atrophy with no symptomatic stroke or silent infarction. 34,35 The previous studies 26,30,31,[36][37][38][39] and the results of our study have shown that atrial fibrillation was associated with an increased risk of poststroke dementia. Moreover, the result of this study found that stroke patients with atrial fibrillation risk of dementia were 1.68 times compared with stroke patients without atrial fibrillation statistically significant.…”
Section: Discussionsupporting
confidence: 54%
“…11,18,22 A study on frequency and predictors of dementia after ischemic stroke showed that prior stroke was independent predictors of dementia (OR 2.53, 95%CI; 1.42 to 4.51). 26 Recurrence stroke risk factors were significantly associated with post-stroke dementia. 11,22,25 In systematic review and meta-analysis, it was found that recurrence stroke was associated with dementia (OR 2.3, 95%CI; 1.5-3.5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations